Spatial Learning Promotes Adult Neurogenesis in Specific Regions of the Zebrafish Pallium - Mazzitelli-Fuentes, Laura S.; Román, Fernanda R.; Castillo Elías, Julio R.; Deleglise, Emilia B.; Mongiat, Lucas A. (Frontiers in Cell and Developmental Biology, 2022)
Adult neurogenesis could be considered as a homeostatic mechanism that accompanies the continuous growth of teleost fish. As an alternative but not excluding hypothesis, adult neurogenesis would provide a form of plasticity necessary to adapt the brain to environmental challenges. The zebrafish pallium is a brain structure involved in the processing of various cognitive functions and exhibits extended neurogenic niches throughout the periventricular zone. The involvement of neuronal addition as a learning-related plastic mechanism has not been explored in this model, yet. In this work, we trained adult zebrafish in a spatial behavioral paradigm and evaluated the neurogenic dynamics in different pallial niches. We found that adult zebrafish improved their performance in a cue-guided rhomboid maze throughout five daily sessions, being the fish able to relearn the task after a rule change. This cognitive activity increased cell proliferation exclusively in two pallial regions: the caudal lateral pallium (cLP) and the rostral medial pallium (rMP). To assess whether learning impinges on pallial adult neurogenesis, mitotic cells were labeled by BrdU administration, and then fish were trained at different periods of adult-born neuron maturation. Our results indicate that adult-born neurons are being produced on demand in rMP and cLP during the learning process, but with distinct critical periods among these regions. Next, we evaluated the time course of adult neurogenesis by pulse and chase experiments. We found that labeled cells decreased between 4 and 32 dpl in both learning-sensitive regions, whereas a fraction of them continues proliferating over time. By modeling the population dynamics of neural stem cells (NSC), we propose that learning increases adult neurogenesis by two mechanisms: driving a chained proliferation of labeled NSC and rescuing newborn neurons from death. Our findings highlight adult neurogenesis as a conserved source of brain plasticity and shed light on a rostro-caudal specialization of pallial neurogenic niches in adult zebrafish.